Photoselective Shade Films Mitigate Heat Wave Damage by Reducing Anthocyanin and Flavonol Degradation in Grapevine (Vitis vinifera L.) Berries - Marigliano, Lauren E.; Yu, Runze; Torres, Nazareth; Tanner, Justin D.; Battany, Mark; Kurtural, Sahap Kaan (Frontiers in Agronomy, 2022)
Wine grape production is challenged by forecasted increases in air temperature and droughts due to climate change and photoselective overhead shade films are promising tools in hot viticulture areas to overcome climate change related factors. The aim of this study was to evaluate the vulnerability of ‘Cabernet Sauvignon’ grape berries to solar radiation overexposure, optimize shade film use for preserving berry composition. An experiment was conducted for two years with four shade films (D1, D3, D4, D5) with differing solar radiation spectra transmittance and compared to an uncovered control (C0). Integrals for leaf gas exchange and mid-day stem water potential were unaffected by the shade films in both years. At harvest, berry primary metabolites were not affected by treatments applied in either year. Despite precipitation exclusion during the dormant seasons in shaded treatments, and cluster zone temperatures reaching 58oC in C0, yield was not affected. Berry skin anthocyanin and flavonol composition and content were measured by C18 reversed-phase HPLC. In 2020, total skin anthocyanins (mg⸳berry-1) in the shaded treatments were 27% greater than C0 during berry ripening and at harvest. Conversely, flavonol content in 2020 decreased in partially shaded grapevines compared to C0. Berry flavonoid content in 2021 increased until harvest while flavonol degradation was apparent from veraison to harvest in 2020 across partially shaded and control grapevines. Untreated control showed lower di- to tri-hydroxylated flavonol ratios closer to harvest. Our results provided evidence that overhead partial shading of vineyards mitigate anthocyanin degradation by reducing cluster zone temperatures and is a useful tool in combatting climate change in hot climate regions.